Reversible Integration of Microfluidic Devices with Microelectrode Arrays for Neurobiological Applications - Grygoryev, K.; Herzog, G.; Jackson, N.; Strutwolf, J.; Arrigan, Damien; McDermott, K.; Galvin, P. (Springer, 2014)
The majority of current state-of-the-art microfluidic devices are fabricated via replica molding of the fluidic channels into PDMS elastomer and then permanently bonding it to a Pyrex surface using plasma oxidation. This method presents a number of problems associated with the bond strengths, versatility, applicability to alternative substrates, and practicality. Thus, the aim of this study was to investigate a more practical method of integrating microfluidics which is superior in terms of bond strengths, reversible, and applicable to a larger variety of substrates, including microfabricated devices. To achieve the above aims, a modular microfluidic system, capable of reversible microfluidic device integration, simultaneous surface patterning and multichannel fluidic perfusion, was built. To demonstrate the system’s potential, the ability to control the distribution of A549 cells inside a microfluidic channel was tested. Then, the system was integrated with a chemically patterned microelectrode array, and used it to culture primary, rat embryo spinal cord neurons in a dynamic fluidic environment. The results of this study showed that this system has the potential to be a cost effective and importantly, a practical means of integrating microfluidics. The system’s robustness and the ability to withstand extensive manual handling have the additional benefit of reducing the workload. It also has the potential to be easily integrated with alternative substrates such as stainless steel or gold without extensive chemical modifications. The results of this study are of significant relevance to research involving neurobiological applications, where primary cell cultures on microelectrode arrays require this type of flexible integrated solution.